Menstruation and impurity: regular abstention from the cult according to Leviticus 15:19-24 and some examples for the reception of the biblical text in early Judaism - Hieke, Thomas (Religion and female body in ancient Judaism and its environments, 2015)
The biblical instructions in Leviticus 15:19-24 about women's regular shedding of the uterine lining and their religious activity mostly refer to male conceptualizations of the female body in Antiquity: The male concepts consider women during their menses as unable to participate in the cult. The woman's status during this period is called "impure." The paper presents the overall structure of Leviticus 15, a short note about the origin of the text, and an exegesis of Leviticus 15:19-24: What exactly do the biblical prescriptions regulate and what was the impact for everyday life? Finally some examples demonstrate the reception of this biblical passage in Early Judaism.